The Integration of Generative AI in Legal Practice: Opportunities and Challenges - White, Alan Robert; Darodjat, Tubagus Achmad; Yuhelson, Yuhelson (Journal Evidence Of Law, 2025)
Generative Artificial Intelligence (GenAI) has emerged as a transformative tool within the legal profession, enhancing productivity and shifting the dynamics of legal service delivery. This desktop review synthesizes recent literature on AI adoption in law firms, focusing on the potential of GenAI in automating routine tasks, the challenges of ethical concerns, and the role of policy and education in mitigating risks. While AI presents numerous opportunities, it also requires careful integration into legal workflows to ensure compliance with ethical standards and professional obligations. This paper explores the current state of GenAI in the legal field and offers insights into future directions, including necessary policy development and professional training.